Walking Speed Reliably Measures Clinically Significant Changes in Gait by Directional Deep Brain Stimulation - Hurt, Christopher P.; Kuhman, Daniel J.; Guthrie, Barton L.; Lima, Carla R.; Wade, Melissa; Walker, Harrison C. (Frontiers in Human Neuroscience, 2021)
Walking speed could represent a simple, integrated tool to assess deep brain stimulation (DBS) efficacy although this measure is often unreported during DBS programming. Here we investigate whether stimulation with a novel directional lead produces reliable and clinically relevant changes in gait function during device activation. Nineteen patients underwent unilateral subthalamic nucleus DBS surgery. Participants arrived off dopaminergic medications pre-operatively and for device activation one-month after surgery. We measured comfortable-walking speed using an instrumented walkway at pre-operation baseline, DBS off and each of 10 stimulation configurations (6 directional contacts, 2 virtual rings, 2 circular rings). Repeated measures ANOVA contrasted walking speed prior to device activation versus the maximum and minimum comfortable walking speeds measured within each DBS configuration. Intraclass correlation coefficients tested walking speed reliability across the four trials within each DBS configuration. We also assessed whether changes in walk speed were a function of increased step length or decreased step time. Mean comfortable walking speed improved significantly with DBS on versus, DBS off, and minimum speeds with DBS on and DBS pre-operatively (p<0.000). Pairwise comparisons showed no significant difference between DBS off and minimum comfortable walking speed with DBS on (p=1.000), and intraclass correlations were ≥ 0.949 within each condition. Scaling step length primarily led to changes in walk speed. Acute assessment of walking speed is a reliable, clinically meaningful measure of gait function during DBS activation. Unilateral subthalamic DBS acutely results in clinically significant changes in walk speed with an appropriately selected DBS configuration (i.e., ring or contact).